Mom and pop stores: economic and social dynamics in a neighborhood of Temuco, in southern Chile - Davinson Pacheco, Luis Guillermo (2020)
The article addresses mom and pop stores, through an ethnographic study, in a neighborhood called: Villa Los Creadores, in Fundo El Carmen from Temuco city in southern Chile. In this framework, the objective is to take a closer look into the growing problematization experienced by these initiatives, where undervaluation prevails, changes in consumption patterns, the socio-economic impacts before an unequal competition, the lack of government support, and the invisibility that tends to manifest on these merchants. So, through four axes, it deepens on: validity; mechanisms that allows its operation; commercial logic and technological resources. The results and conclusions confirm the validity and projections of this small-scale economy; the ways of coexistence that in the framework of globalization they assume with competition; the patterns of neighborhood coexistence around the commercial relationship and the generation of neighborhood identity from the mom and pop stores. Also, the multiplicity of functions of the family appears in these initiatives, the modifications to the physical spaces and the use of Social Networks as an advertising mechanism.